A practical guide to greener theatre : introduce sustainability into your productions - Jones, Ellen E., 1959- (Focal Press, 2014)
"We all want to do our part to protect the environment, but the information you need to be environmentally-savvy in your theatrical production is often scattered across numerous internet pages. Now information on how to green your shows has been compiled in one go-to source! A Practical Guide to Greener Theatre: Introduce Sustainability Into Your Productions shows you how to make greener decisions based on your production process. Each production area is treated in individual chapters, including the scene shop, paint shop, lighting, and technical direction. Checklists help you assess your organization's process; step-by-step instructions guide you through identifying the production areas where manageable changes (with an emphasis on sustainability) will make your productions greener; advice from multiple experts with experience greening their own productions leaves you confident that your processes are environmentally sound. Even non-technical people, who find themselves responsible for supervising productions, will find green solutions that can be instituted with a staff of volunteers or students. Remember: every step toward sustainability is a step forward"--